Pengaruh Harga Terhadap Keputusan Pembeliaan Online Melalui Minat Beli Sebagai Variable Intervening dalam Pandangan Ekonomi Islam Pada Pengguna Aplikasi Buka Lapak di Semarang - Soraya, Tsummadana Mita; Yoestini, Yoestini (ITB AAS INDONESIA Surakarta, 2024)
The era of the dynamic marketing revolution has helped make people more brand conscious in most of the products they buy. Before deciding to buy a product, customers associate it with many factors, making it difficult for marketers to predict how consumers will buy a particular product. The aim of this research is to find out whether price influences purchasing decisions, and to find out whether purchasing interest is able to mediate price on purchasing decisions. The population in this study were Bukalapak users in Semarang City. The number of samples in this research was 140 respondents using accidental sampling technique. Data collection techniques use questionnaires and observation methods. The data analysis method uses multiple linear regression with a path analysis approach and the SPSS program. The research results show that the price variable has an influence on purchasing decisions, then buying interest also has a positive and significant influence on purchasing decisions. The results of the indirect influence test also show that purchasing interest is able to mediate the relationship between price and purchasing decisions. Implementing fair, reasonable and acceptable prices will influence Bukalapak users' purchasing decisions. Purchase interest also influences purchasing decisions and can mediate the relationship between price and purchasing decisions.